Aktor jako cyfrowa marioneta, czyli Edward Gordon Craig w kinie przyszłości - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
Screen actor as a digital puppet? From one point of view, that potentially becomes an interesting platform for modern way of spectacularity and for communications. From another, it’s something destructive and dangerous for the film art. Marek Hendrykowski’s essay analyzes possible consequences of new era of digital actorship in the shadow of its fundamental question and challenge: what happens with man in this form of moving pictures creation.